Significance of Prospective Income Data. - Peterson, William A. (The Accounting Review, 1966)
The measurement of net income is a perplexing problem because it is hard to find a single acceptable meaning that will form the basis for the development of a theory of income measurement. But accountants themselves are partly to blame for confusion. They are often distracted in their practice by preconceived notions of income, taxable income, economic income, and cash flow. It is not surprising those interpretations of accounting reports by the investing public are varied and confusing. The purpose of this article is to present a case for a new approach to corporate reports of income. This approach will be tested by observations of its' impact on depreciation accounting and by its' implications in the resolution of certain important practical accounting problems. Certain accounting principles will be developed for the purpose of measuring prospective income, but their final significance rests on their validity in the measurement of income on a historical basis. This approach permits the use of the present structure of accounting theory for all those expenses and revenues that would be matched the same way in the dimension of expectations as in the dimension of fact.